Occupational Hazards and Safety: How Knowledgeable are Quarry Workers on Accident Prevention at Work in Nigeria? - Samuel Adesina Okueso; Johnson Fejoh (Journal of Social Behavior and Community Health, 2024)
Background: The increased number of quarry activities in Ogu State Nigeria without the commensurate provision of safety resources is an issue of great concern to public health. This study examines the occupational health and safety risks related to quarrying activities among workers. Methods: A cross-sectional survey research design was used, The instrument for data collection was a structured questionnaire developed by the researchers which were: The Knowledge of Occupational Safety and Health-Hazards Questionnaire (KOSHQ) (r = 0.75) and Relationship between Occupational Hazards and Psychological Well-Being Questionnaire (ROHPWQ) (r = 0.84). Descriptive statistics of percentage/frequency were used to describe the demographic characteristics of the participants while Pearson Product Moment correlation was used to test the hypotheses Results: The findings of the study showed that there was a strong, positive, and significant relationship between knowledge of occupational safety, health hazards, and the health of quarry workers (r = 0.940, p-value < 0.05); also, there was a very strong, positive, and significant relationship between occupational hazards and psychological well-being of quarry workers (r = 0.911, p-value < 0.05). a very strong, positive, and significant relationship was observed between knowledge of occupational safety, health hazards, and the health of quarry workers (r = 0.940, p-value < 0.05), there also exists a very strong, positive and significant relationship between occupational hazards and psychological well-being of quarry workers with (r = 0.911, p-value < 0.05). Conclusion: The study concluded that the level of awareness about occupational hazards was The study, recommends that employers provide more training.